Determination of drying and rehydration characteristics of eggplant slices - Doymaz, Ibrahim; Aktas, Cansu (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2018)
In this study, drying characteristics of eggplant slices were investigated by using cabinet dryer. The eggplant slices were pretreated with citric acid solution and blanching in the hot water before drying process. Then, the pretreated and untreated samples were dried in the hot air dryer at 40, 50, 60 and 70 degrees C temperatures. The results showed that the increase in air temperature and pretreatment reduced the drying time and increased rehydration capacity. Moreover, it was observed that the drying temperature and pretreatment affected the colour values. Effective diffusion coefficient values ranged from 2,28X10(-10) to 9,52X10(-10 )m(2)/s, and increased with the increase in air temperature. The values of activation energy were calculated as 26,1432,69 kJ/mol.
Keywords: Activation energy; effective moisture diffusivity; eggplant; drying; rehydration; AIR TEMPERATURES; THIN-LAYERS; KINETICS; DRYER; PRETREATMENTS; SHRINKAGE; SELECTION; Engineering